Does chronic exposure to high levels of nitrogen dioxide exacerbate the short-term effects of airborne particles?. Issue 11 (8th August 2016) - Faustini, Annunziata; Stafoggia, Massimo; Renzi, Matteo; Cesaroni, Giulia; Alessandrini, Ester; Davoli, Marina; Forastiere, Francesco
Abstract : Background: Long-term exposure to air pollutants has been hypothesised as a factor in susceptibility to short-term exposure to particulate matter (PM), but results are not coherent. We studied the short-term effects of PM10 on mortality and assessed whether long-term exposure to nitrogen dioxide (NO2 ) modifies this association. Methods: We used a case-crossover design to evaluate daily PM10 -related mortality among 124 432 35+ year-old participants who died in Rome between 2001 and 2010 and maintained the same address for at least 5 years before death. Modification of PM10 -related mortality by long-term NO2 exposure was determined by two-way interaction, while a three-way interaction was used to assess effect modification of high NO2 levels in population groups defined by sociodemographic position and pre-existing diseases. Results: Mortality increased by 0.82% (0.23–1.41%) for each 10 µg/m 3 increase in PM10 . Mortality rose by 1.22% (0.17–2.38%) in participants exposed to NO2 levels ≥50 µg/m 3 and by 0.69% (0.03–1.34%) in those exposed to levels <50 µg/m 3 with no effect modification (p-interaction 0.378). A suggestion of effect modification was seen in 85+-year-olds (3.10%; p-interaction 0.043), as well as in those with a pre-existing arrhythmia (3.26%; p-interaction 0.014) and chronic obstructive pulmonary disease (3.52%; p-interaction 0.042). Conclusions: Long-term exposure to NO2 is not likely to induce susceptibility to short-term PM10 exposure in the overall population. However, an effect modification of NO2 is probable in the elderly and in those suffering from arrhythmias and chronic obstructive pulmonary disease.